2015
DOI: 10.1016/j.addbeh.2015.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and teen pregnancy in the United States: Evidence from the NSDUH 2002–2012

Abstract: Introduction Few, if any, studies have systematically examined the relationship between substance use and teen pregnancy using population-based samples. We aim to provide a comprehensive examination of substance use among pregnant adolescents in the United States. Method Employing data from the National Survey on Drug Use and Health between 2002 and 2012 (n = 97,850), we examine the prevalence of past 12-month and past 30-day substance use and substance use disorders among pregnant and non-pregnant adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 66 publications
4
44
0
4
Order By: Relevance
“…Nationally, SalasWright and colleagues [43] showed that pregnant teens were significantly more likely than non-pregnant adolescents to have met criteria for alcohol and cannabis disorders, which is often a result of heavier use. Their work suggests that substance use often continues during pregnancy; those findings combined with our findings of particularly high rates of pregnancy among alcohol and marijuana using youth suggest that importance of screening and joint intervention efforts that focus both on substance use and pregnancy prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Nationally, SalasWright and colleagues [43] showed that pregnant teens were significantly more likely than non-pregnant adolescents to have met criteria for alcohol and cannabis disorders, which is often a result of heavier use. Their work suggests that substance use often continues during pregnancy; those findings combined with our findings of particularly high rates of pregnancy among alcohol and marijuana using youth suggest that importance of screening and joint intervention efforts that focus both on substance use and pregnancy prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms such as correlation of SCZ risk with socioeconomic status and other environmental and biological factors might also influence the genetic relationship between SCZ and AFB. For instance, SCZ risk could predispose to impulsive behaviour 29 and substance use 27 that are associated with early pregnancy and childbirth 28 . On the other hand, poor social competence in SCZ might delay the time to meet a partner and/or have offspring, causing delayed AFB.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to those who do not smoke tobacco during pregnancy, pregnant women who smoke tobacco are more likely to be white, unmarried, have other smokers in the household, and report elevated stress levels, and depression (Blalock, Robinson, Wetter, & Cinciripini, 2005;Colman & Joyce, 2003;Orr, Newton, Tarwater, & Weismiller, 2005;Tong, Jones, Dietz, D'Angelo, & Bombard, 2009;Zhu & Valbo, 2002). Although research suggests that pregnant adolescents are less likely to use any substance during pregnancy if they report higher parental involvement and greater school engagement and academic performance and are in their second or third trimester (Salas-Wright, Vaughn, Ugalde, & Todic, 2015;Salas-Wright, Vaughn, & Ugalde, 2016), limited research has compared the rates or correlates of alcohol and tobacco use during pregnancy between adolescents and adults.…”
Section: Prior Research On the Correlates Of Alcohol And Tobacco Use mentioning
confidence: 99%